Comparison between traditional texture methods and deep learning descriptors for detection of nitrogen deficiency in maize crops - Condori, RHM (2017)
Rayner would like to thank Cienciactiva, an initiative of the National Council of Science, Technology and Technological Innovation-CONCYTEC (Peru) for the financial research support and scholarship.